Trefoil System for the Treatment of Mandibular Edentulism: A Case Report with 30 Months Follow-Up - Andrea E. Borgonovo; Simone L. M. Galbiati; Dino Re (Hindawi Limited, 2020)
The purpose of this work is to describe a clinical case of full-arch mandible rehabilitation with a fixed prosthesis on three implants. The chosen protocol is the Trefoil system by Nobel (Nobel Biocare, Zurich, Switzerland) that allows to realize a mandibular fixed rehabilitation on three particularly designed fixtures through the use of prefabricated surgical guides and a preassembled bar on which the prosthesis is built. Both surgical and prosthetic procedures were completed without complications, and after 30 months, the rehabilitations are in good health conditions. The patient is able to maintain a good level of hygiene and is satisfied with the work from an aesthetic and functional point of view.